Experimental and analytical evaluation of a gas-liquid energy storage (GLES) prototype. (1st June 2021) - Vallati, A.; de Lieto Vollaro, R.; Oclon, P.; Taler, J.
Abstract: In this paper, a novel gas-liquid compressed air energy storage prototype, installed in the laboratory of DIAEE Department of Sapienza University of Rome, is studied. Similar to the Compressed-Air Energy Storage (CAES), the Gas-Liquid Energy Storage (GLES) technology is based on gas compression/expansion, where the liquid-piston compression and expansion are utilized. This paper reports on the experimental performance of the first GLES prototype and presents the results from a validated mathematical model. The results show that the proposed system has a high energy efficiency (indicated) over 90%, and then to achieve high values of round trip efficiency (RTE), it is important to improve and optimize the efficiency of the auxiliaries (Motor/Pump and Turbine/Generator). Two different Test, with two different speed of charging phase were done. From the results of the experimental measurements done with the prototype built in the laboratory of the DIAEE Department of Sapienza University of Rome, it can be seen that for slow compression the RTE of the system is around 72%, instead for the fast compression phase, the RTE is around 70%. A mathematical model was implemented and tested with the experimental measurements. From results it can be seen a good agreement between the experimental and numerical analysis, with a maximum error in the Test B (slow compression) equal to 2.5% and 1% respectively for charging and discharging phase. From the parametric analysis it can be seen that only the volume of the tank and the pressure ratio are needed to predict the round trip efficiency of the system. Highlights: A novel prototype of an energy storage system (CEAS) where the air is compressed by liquid is presented. Energy storage (compression) achieved via liquid piston with hydraulic pump. Energy recovery (expansion) achieved passing liquid through hydraulic turbine. A validated mathematical model of the system is presented. Experimental and simulated system performance are presented.